2023
DOI: 10.5535/arm.22127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Home-Based Boxing Training on Trunk Performance, Balance, and Enjoyment of Patients With Chronic Stroke

Abstract: Objective To investigate the effect of 6 weeks of home-based boxing training on trunk performance, balance, fear of falling, and level of therapy enjoyment in individuals with chronic stroke. Methods Eighteen participants with chronic stroke were randomly divided into boxing and control groups (9 patients per group). The boxing group received home-based boxing training for 25 minutes plus balance and trunk exercise training for 15 minutes, while the control group received only home-based balance and trunk exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A randomized controlled trial found that seated boxing improved upper limb strength, balance, and gait in stroke patients [43]. Aerobic boxing requires the participant to control the COG to prevent the body from swinging out of balance with the upper limbs [44,45]. At the same time, our game required participants to make immediate judgments about the icons on the screen, and the receptors in the handle also scored the participants' movements, requiring more sensory involvement in the decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial found that seated boxing improved upper limb strength, balance, and gait in stroke patients [43]. Aerobic boxing requires the participant to control the COG to prevent the body from swinging out of balance with the upper limbs [44,45]. At the same time, our game required participants to make immediate judgments about the icons on the screen, and the receptors in the handle also scored the participants' movements, requiring more sensory involvement in the decision-making process.…”
Section: Discussionmentioning
confidence: 99%